A note on the defect sensitivity of brittle solid foams. (1st February 2019) - Chen, Shaohui; Isaksson, Per
Highlights: The influence of crack length on foams' global fracture behavior is numerically analyzed. The fracture behavior of foams with short cracks deviates from classical fracture theories. A defect of about three times the average cell size is needed to localize continued crack growth to the defect. Abstract: The fracture behavior of brittle solid foams of different densities and regularities is numerically analyzed in finite element models. The findings provide insight into the complex fracture phenomenon in cellular materials and reveal a size influence from a dominant microstructure on the global fracture mechanism. It is observed that a crack of length of about three times the average cell size in the foam is needed to obtain localization of nucleated fractures to the vicinity of the initial defect. At cracks smaller than this critical size, the fractures nucleate at randomly positioned high-stressed regions in the foam far away from the initial crack, i.e. the structure is seemingly insensitive to the initial defect. Further, it is found that irregular (i.e. randomly positioned cells) foams are more insensitive to defects than perfectly ordered foams if all other parameters are similar and thus indicate that classical fracture theories for solid foams have to be slightly modified.